THE RELATIONSHIP BETWEEN AGE AND PUBLIC KNOWLEDGE OF RHEUMATIC DISEASE IN MALANG 2017 - Thariq, Diefa Muhammad; Aditya, Perdana; Mayangsari , Elly (Universitas Brawijaya, 2024)
Rheumatic disease is a type of illness that affects the human musculoskeletal system. Rheumatic diseases are often associated with advancing age. This categorizes rheumatic diseases as conditions more prevalent among the elderly. Symptoms include pain and can be accompanied by redness, swelling, and other manifestations. Knowledge about a disease can prevent and reduce the risk of its occurrence. Age is one of the factors that can influence the level of knowledge about a disease. This study aims to determine the relationship between age and public knowledge, as well as the influence of age on the improvement of public knowledge about rheumatic disease. The study employed an analytical observational approach with a cross-sectional design. Data were collected from pre-test and post-test questionnaires distributed during a public seminar on rheumatic disease at the Faculty of Medicine, Brawijaya University, on October 8, 2017. The results indicated that the highest level of rheumatic disease knowledge was in the age range of 25-54 years. Moreover, the highest increase in knowledge was observed in the age range of <25-34 years. Spearman rank correlation analysis revealed no significant relationship between age and the increase in knowledge about rheumatic disease. However, the Wilcoxon test results indicated that the age range of 55->65 years exhibited a significant difference between pre-test and post-test scores. For future research, questionnaire validation before assessing knowledge levels is recommended.